Pemikiran Ki Bagus Hadikusumo tentang Moderasi Beragama Materi Komitmen Kebangsaan dan Implementasinya dalam Pembelajaran Pendidikan Agama Islam - Azis, Abdul; Kurniawan, Raden Muhammad Ardiyansyah (IAIN Batusangkar, 2025)
The relationship between Islam and the Indonesian state is evidenced by the establishment of Islamic governments, even Islamic kingdoms, which are a manifestation of their sincere efforts to implement the basic teachings of the Koran and Sunnah. In this study, the author uses a qualitative method by using library research (library research). Researchers in data analysis using analytical methods where this method is carried out by identifying information objectively. The result of this discussion is the implementation of Ki Bagus Hadikusumo's thoughts on religious moderation of national commitment material in learning Islamic Religious Education includes the following five aspects: first, tawhid or aqidah. First, tawhid or aqidah. Learners must hold fast to their beliefs and always call for worshiping Allah and always being grateful to enjoy the sustenance that has been given by Allah Ta'ala. Second, learners must have the character of a leader in accordance with the character of the Prophets. Third, students must have a clear vision in life based on the Qur'an and Sunnah. Fourth, the contribution of thought. The importance of students in maximizing knowledge which is manifested in the contribution of ideas for the welfare of the country and its people. Fifth, good and clean politics, so that students must have good and clean political thinking that can carry out laws in accordance with Islam based on the Qur'an and Sunnah so as to create justice, brotherhood, equality, deliberation, plurality, peace, and accountability. So that the implementation of Ki Bagus Hadikusumo's thoughts on religious moderation of national commitment material in learning Islamic Religious Education five points or the core that has been mentioned above so that students always encourage to carry out religious teachings as a whole and peacefully, and have an active role in maintaining unity, justice, and peace within the framework of the Unitary State of the Republic of Indonesia.